Multiple Intelligences Theory Intelligence Formed in Economic Subjects - Amrullah, Haris (Universitas Pendidikan Indonesia, 2021)
Each discipline has different characteristics and requires different bits of intelligence. Each discipline must have one or more intelligence that has the potential to be developed based on the characteristics of the discipline. In this study, the discipline that will be taken is economics. This article is a study that aims to find out what types of intelligence will develop in economics learning according to the characteristics of economics learning. This research is a qualitative type of research that is a literature study whose primary object is obtained from the existing literature. Systematic, clear, logical, and factual information is needed in qualitative research. In the study, it was found that learning economics which has analytical characteristics that generally use problem-solving methods has the potential to highlight multiple intelligences in students who are trained based on the character of the economics subject itself. This intelligence includes linguistic, logical-mathematical, spatial, interpersonal, personal, and naturalist intelligence.